EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN ARTIFICIAL INTELLIGENCE TERHADAP KETERAMPILAN MENYUSUN SURAT BISNIS PADA KELAS X MPLB SMK NEGERI 2 SEMARANG - Winarsih Handayani Afifah; Teguh Hardi Raharjo (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effectiveness of an Artificial Intelligence-assisted Problem-Based Learning model in improving the business letter writing skills of X MPLB program at SMK Negeri 2 Semarang. The study employes a quantitative approach using a quasi-experimental design of the non-equivalent posttest-only control group type. The total sample consisted of 72 students, divided into an experimental group (36 students) and a control group (36 students). Assessment was conduted using a practical skills test involving case study analysis and the drafting of business letters. Data analysis employed an independent sample t-test on posttest scores, revealing a hinghly significant difference. An independent t-test on the posttest results for business letter drafting skills between the experimental group (M = 91.19) and the control group (M = 84.25) yielded a t-value of 4.583 and a p-value of 0.000. These findings indicate that the Artificial Intelligence-assisted Problem-Based Learning model effectively enhances students’ correspondence skills, particularly in facilitating brainstorming of ideas and editing formal vocabulary. This study recommends the routine integration of AI in correspondence practice learning to strengthen digital literacy and higher-order thinking skills in vocational education.